Evaluation of the spiritual extracurricular program in Madrasa - Fatimah, Siti; Yuberti, Yuberti; Ayu, Sovia Mas (Universitas Islam Negeri Raden Intan Lampung, 2021)
Spiritual extracurricular activities have an important role in exploring potential interests, talents, and can encourage the increase in the values of the religious character of students and their practice of Islamic teachings which have declined in recent times. The purpose of this study was to determine how to evaluate the context, input, process, and product of the Spirituality extracurricular program at Madrasa Tsanawiyah Darul Huda Bandar Lampung. This study used an evaluative design with a descriptive approach. Data collection techniques used were interviews, questionnaires, observation, and documentation. The subjects of this study were the head of the madrasa, coaches, and spiritual extracurricular participants. Data were analyzed using Miles and Huberman’s theory, namely reducing data, presenting data, and drawing conclusions / verifying. The results showed: (1) Evaluation of the context related to program management structure, program objectives, types of activities, work programs, and needs was quite good, (2) Evaluation of inputs related to supervisors and participants who took part in spiritual extracurricular activities, as well as feasibility/completeness. from the facilities and infrastructure to support program activities is quite good. However, it needs to be improved in the provision of teacher trainers, and the details of program implementation funding, (3) Evaluation of the process is good. The implementation is by the program guidelines of The Ministry of Education and. Culture Number 62 of 2014, (4) Good product evaluation, containing student learning outcomes as values, achievements, and the character of students from religious character, honesty, discipline, responsibility, tolerance, cooperation, polite/polite, and self-confidence. The implication of this research shows that the spiritual extracurricular program at Madrasa Tsanawiyah Darul Huda Bandar Lampung plays a very important role in shaping the religious character of students.